Testomalacia - Sanjay Kalra; Atul Dhingra; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
In this communication, we introduce the descriptive diagnostic term ‘testomalacia’. Testomalacia may suggest softness of the testes, both anatomic and/or functional, or may suggest malaise or illness related to testosterone secretion/function. While the term is not in vogue as of now, we feel that it describes functional androgen deficiency in an apt manner. Unlike other terms used to describe these symptoms, testomalacia can be used at any age, encompasses several etiologies and is just a single term rather than multiple complicated abbreviations. Keywords: Hypogonadism, Late Onset Hypogonadism (LOH), Male Health, Testes, Testosterone, Testosterone Deficiency